Accumulation of cadmium in growing peanut (Arachis hypogaea L.) seedlings - its effect on lipid peroxidation and on the antioxidative enzymes catalase and gualacol peroxidase - Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Journal of Plant Nutrition and Soil Science, 2008)
In plants exposed to high metal concentrations, mechanisms to counteract the oxidative burst are crucial for its survival. To investigate the temporal sequence of physiological reactions of peanut seedlings (Arachis hypogaea L.) to cadmium exposure, seeds were cultured in increasing concentrations of CdCl(2), ranging from 50 to 300 mu M. Germination frequency was scored, and the distributions of Cd in root, stem, and leaves were determined after 2 and 4 weeks of culture. Lipid peroxidation and activities of antioxidative enzymes including catalase (CAT, EC 1.11.1.6) and guaiacol peroxiclase (GPX; EC 1.11.1.7) were estimated in these three parts of the plant. Germination of seedlings was not affected, but the growth of seedlings was severely suppressed with increasing concentrations of CdCl(2) and incubation period. Pattern of Cd distribution in the three organs varied with concentration and period of exposure to Cd. Increased lipid peroxidation was detected in all parts of the developing seedlings with increasing metal accumulation. Catalase and guaiacol peroxidase activity varied in the three parts of the seedlings with concentration of Cd and incubation period. Guaiacol peroxidase activity appears to be more active in scavenging the reactive oxygen species in developing peanut seedlings. The results of the present experiment demonstrate the advantages of a tissue-culture model system in studying the complex network of interactions of various factors in stress tolerance.
Keywords: Abiotic stress; heavy metal; stress tolerance; TBARS; thiobarbituric acid; Tissue culture

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis

Genetic homogeneity of in vitro raised plants of grapevine cv. crimson seedless revealed by ISSR and microsatellite markers - Nookaraju, A.; Agrawal, Dinesh C. (South African Journal of Botany, 2012)
The present study was conducted to test the clonal homogeneity of six month old tissue culture raised plants of grapevine cv. Crimson Seedless using Inter Simple Sequence Repeat (ISSR) and Simple Sequence Repeat (SSR) markers. Visible assessment of these in vitro raised plants maintained in polyhouse did not show any morphological differences among themselves. However, to test the genetic homogeneity of these plants, we screened 50 ISSR primers out of which, 22 primers produced scorable and repeatable bands. These 22 primers were used further for assessing genetic homogeneity of in vitro raised plants of Crimson Seedless. These 22 ISSR primers generated 134 distinct band classes with a total of 3216 scorable bands. All the primers showed uniform banding pattern for all the in vitro raised plants and the mother plant. In case of 5 SSR primers (VS I, VVMD5, VVS2, VMCNG4c8 and VVMD31) used, a total of 288 scorable bands were obtained. The allele sizes ranged from 98 to 254 bp. Allelic composition of 23 in vitro raised plants and the mother plant at 5 SSR loci did not show any polymorphism. The results of the two marker systems in the present study revealed the genetic uniformity among the in vitro raised plants demonstrating the reliability of in vitro propagation system used for the cultivar. (C) 2011 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Allele composition; Clonal fidelity; Inter Simple Sequence Repeats; Monomorphic bands; Tissue culture; Vitis vinifera L.